2011
DOI: 10.1056/nejmoa1008069
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Blast-Related Traumatic Brain Injury in U.S. Military Personnel

Abstract: BACKGROUND Blast-related traumatic brain injuries have been common in the Iraq and Afghanistan wars, but fundamental questions about the nature of these injuries remain unanswered. METHODS We tested the hypothesis that blast-related traumatic brain injury causes traumatic axonal injury, using diffusion tensor imaging (DTI), an advanced form of magnetic resonance imaging that is sensitive to axonal injury. The subjects were 63 U.S. military personnel who had a clinical diagnosis of mild, uncomplicated traumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
469
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 556 publications
(504 citation statements)
references
References 41 publications
26
469
3
1
Order By: Relevance
“…Conventional CT and MRI are primarily sensitive to blood from nearby torn capillaries, rather than axonal damage itself, hence they underestimate the presence of DAI, especially in mTBI. New approaches using diffusion tensor imaging (DTI), positron emission topography (PET), and macromelecular proton fraction (MPF) have showed promising capability in detecting injuries and/or abnormalities that are not visible in CT and MRI (e.g., Petrie et al, 2014;MacDonald et al, 2011;Davenport et al, 2012;Shenton et al, 2012).…”
Section: Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional CT and MRI are primarily sensitive to blood from nearby torn capillaries, rather than axonal damage itself, hence they underestimate the presence of DAI, especially in mTBI. New approaches using diffusion tensor imaging (DTI), positron emission topography (PET), and macromelecular proton fraction (MPF) have showed promising capability in detecting injuries and/or abnormalities that are not visible in CT and MRI (e.g., Petrie et al, 2014;MacDonald et al, 2011;Davenport et al, 2012;Shenton et al, 2012).…”
Section: Clinicalmentioning
confidence: 99%
“…Conventional CT and MRI are primarily sensitive to blood from nearby torn capillaries, rather than axonal damage itself, hence they underestimate the presence of DAI, especially in mTBI. New approaches using diffusion tensor imaging (DTI), positron emission topography (PET), and macromelecular proton fraction (MPF) have showed promising capability in detecting injuries and/or abnormalities that are not visible in CT and MRI (e.g., Petrie et al, 2014;MacDonald et al, 2011;Davenport et al, 2012;Shenton et al, 2012).Magnetoencephalogram (MEG) is a non-invasive functional imaging technique that directly measures the magnetic signal due to neuronal activation in gray matter (GM) with high temporal resolution (<1 ms) and spatial localization accuracy (2-3 mm at cortical level) (Leahy et al, 1998). MEG demonstrates sensitivity to abnormal neuronal signals resulting from axonal injuries.…”
mentioning
confidence: 99%
“…Structural Neuroimaging of TBI-It is well established that conventional structural imaging techniques, such as computed tomography (CT) and MRI, are unlikely to advance our understanding of combat-related mTBI, as these methods are generally considered to lack sufficient sensitivity to detect the subtle abnormalities that characterize mTBI (Mac Donald, et al, 2011). However, studies of civilians have demonstrated the utility of DTI for examining white matter abnormalities in TBI (e.g., Kraus, Susmaras, Caughlin, Walker, Sweeney, & Little, 2007).…”
Section: Structural and Functional Neuroimaging Of Ptsd And Tbi In Oementioning
confidence: 99%
“…Objective and specific neuroimaging based biomarkers for both disorders would be invaluable for improving diagnosis, subsequent symptom monitoring, and treatment. Additional studies utilizing newer and more advanced imaging technologies will be critical for making such biomarkers a reality (Mac Donald, et al, 2011). Moreover, there is a critical need for studies that use advanced imaging techniques to compare Veterans with PTSD only, TBI only, and co-occurring PTSD-TBI, as such an approach appears essential for disentangling this complex relationship.…”
Section: Future Directionsmentioning
confidence: 99%
“…McCrea et al reported that college football players exhibited cognitive impairment and balance problems after concussion, 12 and although these symptoms resolved, other studies have investigated the effects of repeated insults over time. 13 More recently, in a study of United States military personnel with mild TBI, persistent abnormalities revealed on diffusion tensor imaging (DTI) were consistent with traumatic axonal injury in some subjects, although none had detectable intracranial injury on CT. 14 In a similar study, soldiers with mild TBI were significantly more likely to report poor general health, missed work days, medical visits, and post-concussive symptoms than were soldiers with other injuries, although the effects were confounded by post-traumatic stress disorder (PTSD) and depression. 15 In broader populations of adults with mild TBI, the likelihood of major depressive disorder and epilepsy increased, although effects were also confounded by prior history.…”
mentioning
confidence: 99%